أخلقة الإدارة العمومية كآلية لمكافحة الفساد الإداري في الجزائر - عباد عبد الهادي; بن سادات نصر الدين (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
شهد حقل الدراسات الإدارية زيادة كبيرة في الاهتمام بالمجالات المتعلقة بمكافحة الفساد الإداري والوقاية منه في الإدارة العمومية. ولهدا كان هناك تركيز كبير في العديد من البحوث و الدراسات الأكاديمية، في البحث عن سبل ايجاد آليات وحلول حقيقية لمعالجة أهم المعضلات الأخلاقية والمتعلقة بأهمية تفعيل الجوانب الأخلاقية في مكافحة الفساد الإداري. لذا فالهدف من هذه الدراسة استعراض الآثار الأساسية لتطبيق مبادئ أخلاقيات الإدارة العمومية في الجزائر من أجل تعزيز قيم الشفافية والمساءلة والنزاهة كمبادئ للحوكمة الإدارية Abstract: The field of Administrative studies has witnessed a great interest in fighting and preventing Corruption in public administration. Therefore, there was a considerable emphasis in many researches on how to create an Anti-Corruption mechanisms in order to respond effectively to this dilemma through the promotion of administration ethics. The aim of this study is to review the possible impact and the fruitful outcomes of applying ethics principles in Algerian public administration. with a view to promoting transparency and accountability and integrity as principles of good governance